Evidence‐based genetic counselling implications for Huntington disease intermediate allele predictive test results. (15th January 2014) - Semaka, A.; Hayden, M.R.
<x xml:space="preserve">Abstract</x> Intermediate alleles (IAs) for Huntington disease (HD) contain 27–35 CAG repeats, a range that falls just below the disease threshold of 36 repeats. While there is no firm evidence that IAs confer the HD phenotype, they are prone to germline CAG repeat instability, particularly repeat expansion when paternally transmitted. Consequently, offspring may inherit a new mutation and develop the disease later in life. Over the last 5 years there has been a renewed interest in IAs. This article provides an overview of the latest research on IAs, including their clinical implications, frequency, haplotype, and likelihood of CAG repeat expansion, as well as patient understanding and current genetic counselling practices. The implications of this growing evidence base for clinical practice are also highlighted. These evidence‐based genetic counselling implications may help ensure individuals with an IA predictive test result receive appropriate support, education, and counselling.